2020
DOI: 10.3390/foods9091301
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro α-Glucosidase and α-Amylase Inhibitory Activities of Free and Bound Phenolic Extracts from the Bran and Kernel Fractions of Five Sorghum Grain Genotypes

Abstract: Diabetes is a global health challenge. Currently, an effective treatment for diabetes is to reduce the postprandial hyperglycaemia by inhibiting the carbohydrate hydrolysing enzymes in the digestive system. In this study, we investigated the in vitro α-glucosidase and α-amylase inhibitory effects of free and bound phenolic extracts, from the bran and kernel fractions of five sorghum grain genotypes. The results showed that the inhibitory effect of sorghum phenolic extracts depended on the phenolic concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 38 publications
0
26
1
Order By: Relevance
“…However, these drugs often induce serious gastrointestinal side effects including stomach pain, flatulence, and diarrhea [4]. As a result, natural α-glucosidase and α-amylase inhibitors, mostly from food products, have emerged as promising therapeutic options to supplement or even substitute existing drugs [2,[5][6][7]. Several types of natural plant products have emerged as promising α-glucosidase and α-amylase inhibitors in recent decades [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, these drugs often induce serious gastrointestinal side effects including stomach pain, flatulence, and diarrhea [4]. As a result, natural α-glucosidase and α-amylase inhibitors, mostly from food products, have emerged as promising therapeutic options to supplement or even substitute existing drugs [2,[5][6][7]. Several types of natural plant products have emerged as promising α-glucosidase and α-amylase inhibitors in recent decades [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro α amylase activity was measures using the method described in Xiong et al, (2020) [14] with some modifications as mentioned in Mel et al (2020) [15] and Janarny and Gunathilake, (2020) [16] . A sample of 1.00 mg from each yam, roots and cereal flours were weighed and 100 μl of the αamylase enzyme was added which was prepared by adding 27.5 mg of enzyme in 100 mL of 20 mmol sodium phosphate buffer containing 6.7 mmol of sodium chloride was added (pH 6.9).…”
Section: In Vitro α Amylase Inhibitory Assaymentioning
confidence: 99%
“…[ 19 ]. Aminoguanidine, pimagedine and metformin are examples of synthetic inhibitors for AGEs and acarbose, miglitol and voglibose are synthetic inhibitors for digestive enzymes and have been in use for the past decades [ 20 , 21 ]. However, clinical trials and in vivo experiments demonstrated the side effects of these synthetic inhibitors, such as hepatotoxicity, abdominal distention, flatulence, meteorism, anaemia, vomiting, heart failure, etc.…”
Section: Introductionmentioning
confidence: 99%